Lignin extraction & functional groups study / Nur Alya Balqis Sabri - Sabri, Nur Alya Balqis (2023)
Lignin is second richest natural polymer after cellulose. Research shows the rice husk has a higher of lignin content. The lignin is commonly used in biofuels. From this study, the objectives is to extract the lignin from the rice husk and study the functional group by used an alkaline extraction method. Based on study, the four process parameters of lignin extraction from rice husk that were systematically and completely optimized using the response appear methodology is reaction time, extraction temperature, sodium hydroxide and solid/liquid ratio. For this study, the extraction solution which is a mixture of sodium hydroxide with water with different concentrations of sodium hydroxide: 5%, 10% and 15% were used. The catalyst that used for extraction is sulfuric acid and hydrogen peroxide with a concentration of 5%. Based on the experiment, the functional groups of lignin such as hydroxyl, carbonyl and ether in rice husk waste has been identify. The different types of functional group for lignin samples were characterized by using Fourie-transform infrared spectroscopy (FTIR). The extracted samples show the observation of peak for the two types of mixture solvent (NaOH- H2O2 and NaOH-H2SO4) are slightly different because the different chemical processes. The NaOH-H2O2 treatment mainly leads to oxidation, which can increase the peak, while NaOH-H2SO4 cause to acid hydrolysis that can slightly move or change the peaks.